Adaptations at the shoulder of the throwing athlete and implications for the clinician - Whiteley, R.; Oceguera, M.; Valencia, E.; Mitchell, Tim (Lippincott Williams & Wilkins, 2012)
The shoulders of those involved in repeated forceful overhead throwing undergo a range of neural, muscular, and skeletal adaptations. Knowledge of these normal adaptations may be helpful for the understanding of the prevention and treatment of injury in these athletes. This paper summarizes the current literature regarding these adaptations, and their relation to performance and pathology are presented along with relevant clinical implications. Throwing athletes show alterations in the strength ratio of their internal rotation (IR) compared with external rotation such that IR is enhanced and external rotation remains unchanged (in comparison with their nonthrowing arm). Typical scapular postural changes are seen (often IR and anterior tilting of the scapula) in the throwing arm; the humeral cortical and trabecular bones are thickened and there is often greater humeral retrotorsion. Torsional changes are, however, variable. Throwers have a higher incidence of injury to their suprascapular nerve, which may help explain their relative external rotational weakness. There is some evidence that the posterior inferior capsule is thickened in throwing athletes.